2021
DOI: 10.14393/sn-v33-2021-59688
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-economic indicators and territorial networks at the spatiotemporal spread dynamics of Covid-19 in Brazil

Abstract: This work aims to provide an overview of the territorial evolution of COVID-19 (SARS-CoV-2) in Brazil using socio-demographic variables, for the time span between February 26, 2020 until January 24, 2021. Socio-demographic indicators, basic sanitation infrastructure data, and epidemiological bulletins were integrated using Principal Components Analysis (PCA) to develop a social vulnerability index (SVI), to estimate the degree of exposure risk of the Brazilian population to COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…The introduction of the Delta variant occurred in the first semester of 2021, during a period of restriction relaxation and incomplete vaccine schedules. Despite this, and despite the differences between states with large population concentrations (São Paulo, Rio de Janeiro), others, such as Tocantins, are influenced by the transport of agribusiness products [52,53]. In the case of the latter, the state of Tocantins stands out, as it is considered the last Brazilian agricultural frontier beyond the Amazon [11].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the Delta variant occurred in the first semester of 2021, during a period of restriction relaxation and incomplete vaccine schedules. Despite this, and despite the differences between states with large population concentrations (São Paulo, Rio de Janeiro), others, such as Tocantins, are influenced by the transport of agribusiness products [52,53]. In the case of the latter, the state of Tocantins stands out, as it is considered the last Brazilian agricultural frontier beyond the Amazon [11].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, in the pre-vaccination period of covid-19 there were a high mortality rate in COVID-19 patients aged ≥ 65 years old, present body mass index (BMI) ≥ 40 kg/m 2 , smokers, as well as, among those that were diagnosed with diabetes mellitus, hypertension, cardiovascular disease and immunosuppressed (Rothana & Byrareddy, 2020 ; Souch & Cossman, 2021 ). In addition, COVID-19 seems to affect deeply vulnerable groups, such as those economic and socially disadvantaged, especially in developing countries (Da Guia Albuquerque et al, 2021 ). The US Centers for Disease Control and Prevention study reported that in the US black population may be disproportionately affected by COVID-19 (Garg et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the use of geotechnologies has also proved to be of great value, especially Digital Cartography and Geographic Information Systems (GIS) as tools for georeferencing and spatial representation of the occurrences of COVID-19. Several initiatives have used digital maps and cybercartography for the cartographic organization of data, didactically illustrating the density of the epidemic and, mainly, supporting decision-making in the effective application of control devices to reduce the transmission of the virus [2,9]. Such initiatives, both in the academic sphere and in territorial management, follow an extensive tradition of Health Cartography as a technical-scientific instrument to support epidemiological analysis.…”
Section: Introductionmentioning
confidence: 99%